Analisis Rank Batu Bara dan Potensi Gas Methane pada Lapangan X Formasi Balikpapan - kasmira kasmira (Universitas Sulawesi Barat, 2021)
Coal has ability to store gas in large quantities, because the surface has ability to adsorb gas. This research aimed to investigate and analyze the coal rank and methane gas potentials in Field X of Balikpapan Formation. The research was conducted in Kutai Kartanegara Regency, East Kalimantan Province. The methods used in the research were the approximate and ultimate analyses as well as the gas analysis at the 19 wells containing coals. The 19 wells were divided into 5 sub Formations called ILX. The research results indicated that the coal rank in the research areas was categorized as the sub-bituminous b up to the high volatile bituminous c. The methane gas content was also categorized as great, i.e. 80.86 scf/ton up to 534,99 scft/ton. The analysis results revealed that the deeper the coal bed, the higher the coal rank and the methane gas content. Based on the previously mentioned results, the coal in Field X possessed good quality and hence had the potential to be the reservoir Coal Bed Methane.